2022
DOI: 10.1111/bjso.12611
|View full text |Cite
|
Sign up to set email alerts
|

Why are people ‘Lying Flat’? Personal relative deprivation suppresses self‐improvement motivation

Abstract: The ‘Lying Flat’ mindset refers to people's low intention to self‐improvement. We hypothesized that personal relative deprivation (PRD), the negative consequence of social comparisons, is one of the reasons that might harm individuals' self‐improvement motivations. In study 1 (N = 313), we found that PRD negatively predicted self‐improvement after controlling for various confounding variables. This result is confirmed in study 2a (N = 3399) and 2b (N = 3219) by using a national representative sample. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 98 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Research has also suggested that Chinese Generation Zers possess strong innovative and transformative capabilities in participating in social governance (Li, 2019). On the other hand, along with China's economic rise, “lying flat” [躺平], which depicts the life choice of youth barely being motivated to self‐improvement or giving up active roles in society to avoid intense competition (Zheng et al, 2022; Zhou, 2022), has become a popular term among the younger generation. It is possible that some Generation Zers deliberately chose not to take action to participate actively.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also suggested that Chinese Generation Zers possess strong innovative and transformative capabilities in participating in social governance (Li, 2019). On the other hand, along with China's economic rise, “lying flat” [躺平], which depicts the life choice of youth barely being motivated to self‐improvement or giving up active roles in society to avoid intense competition (Zheng et al, 2022; Zhou, 2022), has become a popular term among the younger generation. It is possible that some Generation Zers deliberately chose not to take action to participate actively.…”
Section: Introductionmentioning
confidence: 99%